SOME FRESHWATER SNAILS FROM NORTHERN IRAN - A. Mansoorian (Tehran University of Medical Sciences, 2000)
There are many freshwater snails involved in the life cycle of parasitic flukes. Some of these animals, such as Bulinus spp and Lymnaea spp are very important in public health and veterinary medicine. For example, Bulinus trucatus and Lymnaeid snails transmit Human Bilharziosis and zoonotic Fascioliosis, respectively. For this reason most freshwater bodies of northern Iran, were searched for potential intermediate host snails of medical parasites. Thirteen mollusc taxa, i.e. 5 operculated shell-bearing versus 8 pulmonated snails were found during a snail survey, in the summer of 1992. Two taxa, viz. Anisus leucostoma and Bulinus truncatus were found to be new species for Iran and northern Iran, respectively.